Molecular characterization of the horse isolate of Echinococcus granulosus in Turkey - Utuk, A. E.; Simsek, S. (Cambridge Univ Press, 2013)
Cystic echinococcosis is one of the most important helminthozoonoses, affecting various species of intermediate hosts and humans. In this report, we present Echinococcus granulosus infection in a horse and its molecular characterization. Polymerase chain reaction (PCR) amplification of mitochondrial 12S rRNA (mt-12S rRNA) and partial sequencing of mitochondrial cytochrome c oxidase subunit 1 (mt-CO1) genes were performed. According to the mt-12S rRNA-PCR result, the horse isolate was grouped with E. granulosus sensu stricto (G1-G3) and the partial mt-CO1 sequence corresponded to the G1 strain. This is the first study of the molecular characterization of the horse isolate of E. granulosus in Turkey.
Keywords: Cystic Echinococcosis; Genus Echinococcus; Great-Britain; Transmission; Taxonomy; Equids; East